A novel concept for the manufacture of individual sapphire-metallic hip joint endoprostheses. - Mamalis, A. G.; Ramsden, Jeremy J.; Grabchenko, A. I.; Lytvynov, L. A.; Filipenko, V. A.; Lavrynenko, S. N. (Jointly by, Collegium Basilea (Institute of Advanced Study) and Association of Modern Scientific Investigation., 2006)
At the present time, artificial joints made with metallic, ceramic, metal-polymeric or ceramicpolymeric friction pairs substituting for the natural biomechanic articulations "head of the hip joint-acetabulum" are widely used for endoprosthetic operations on hip joints. Experience gained in the course of more than 2000 operations has shown that along with the advantageous properties of modern endoprosthetic constructions made of metal, ceramics and polymers, they have certain drawbacks. Among them are insufficient biological inertness and susceptibility to excessive wear of the friction pair components. In addition, as a result of wear of the hinge friction pair, toxic and oncologically dangerous products of degradation accumulate in the different organs and tissues. This in turn results in severe complications and demands correspondingly complicated corrective intervention, often leading to worse disability than that which the original operation was designed to cure. The aim of the study reported here was the development and clinical validation of a highly effective and long-lived hip joint endoprosthesis with a sapphire head whose wear capacity is superior to all others. The endoprosthesis consists of a metallic pedicle, a dismountable articulation (metallic necklayer of supramolecular polyethylene-sapphire head) and an acetabular cup. The endoprostheses with the sapphire head proved themselves positively in clinical trials and are considered to be highly promising for future applications.
Keywords: endoprostheses; sapphire; rapid prototyping